Optimalisasi Layanan Penerbitan Nomor Induk Berusaha Sebagai Upaya Pemberdayaan UMKM di Kelurahan Kalisari Surabaya - Gita Kusumaningtyas, Rofifah; Takarini, Nurjanti (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This research discusses the optimization of Nomor Induk Berusaha (NIB) issuance services as a strategy for empowering Micro, Small, and Medium Enterprises (MSMEs) in Kalisari Sub-District, Surabaya. Through a qualitative approach involving interviews and observations with 21 MSME actors and sub-district apparatus, it was found that the NIB issuance process still faces challenges such as lengthy bureaucracy, lack of socialization, and limited digital access. Optimization efforts were carried out through procedure simplification, digital training, and one-stop service integration, which successfully increased NIB issuance by up to 70%. The research results indicate that this optimization not only streamlines business legality but also enhances MSMEs' access to markets, financing, and legal protection, thereby supporting sustainable local economic growth.